Author Correction: A Machine-learning Approach to Forecast Aggravation Risk in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease with Clinical Indicators - Junfeng Peng (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.